(3GdJehjd GdOhdj (B/s - (3GdeTgOGfj, NGdO CMeOs ((3YeGf(B: s (3OGQ GdCjGe ddfTQ hGdJhRjY(B, s, 2012)
(3jVe eGgjI GdJehjd GdOhdj hBaGb JWhQg, JCKjQ GdJehjd GdOhdj Ydi GdJfejI GdGbJUGOjI heGgjI ejRGf GdeOahYGJ hgjcdg, GdCShGb GdeGdjI GdOhdjI hGdEbdjejI , GNJdGd ejRGf GdeOahYGJ hJUMjMg, EOGQI GdNWQ GdSjGSj, SYQ GdUQa, GdGSJKeGQ hGdeUGQa, CKQ GdSjGSI GdfbOjI hGdeGdjI aj GdJfejI GdGbJUGOjI, GdESJKeGQ GdCLfHj GdeHGTQ hGdJehjd GdOhdj, hGbY GdGSJKeGQ GdGLfHj aj GdYQGb HYO YGe (B2003 (3, GdeNGWQ hGdYhGFO, GdHjFI GdeGdjI, GdGShGb GdOhdjI (BWorld Markets(3, GdGYeGd GdOhdjI hGdGShGb GdYGdejI, GdJNWjW GdeGdj heUGOQ GdJehjd, GdeMaXI GdGSJKeGQjI heNGWQ JchfjgG, EOGQI GdLhOI GdGSJKeGQjI , CKQ CReGJ GdfXGe GdQGSeGdj Ydi GdJfejI GdGbJUGOjI aj GdOhd GdfGejI(B.s
(3GdeQGLY U(B.375s
Keywords: (3GdESJKeGQ GdCLfHjs; (3GdJehjd GdOhdjs; (3GdJfejI GdEbJUGOjIs; (3GdeDSSGJ GdeGdjI GdOhdjIs